A Farewell to Arms - Vidor, Charles; Oskar, Homolka; Rock Hudson; Vittorio De Sica; Jennifer Jones (USA Selznick International Pictures, 1957)
Set against the backdrop of the Italian front during World War I, an American Army volunteer (Rock Hudson) meets a British nurse (Jennifer Jones) on the eve of the big offensive in the Alps and they fall passionately in love. Torn apart, then reunited, they escape to Switzerland to await the birth of their child - and the tragic conclusion to their once-in-a-lifetime romance. "Moving and realistic" (The Hollywood Reporter), this sweeping epic remains a powerful and emotional experience.
The story of an affair between an English nurse an an American soldier on the Italian front during World War I.
Ernest Hemingway
Languages: English
Subtitles: English, German, Turkish
Keywords: Drama -- Romance -- War